Enhancing Procedural Text Writing through the Pair Check Method: A Classroom Study in Indonesian Junior Secondary School - Mifta Thoha; Kasmantoni Kasmantoni; Wenny Aulia Sari (JPI: Jurnal Pustaka Indonesia, 2023)
The study aims to investigate the implementation of the Pair Check method as a cooperative learning strategy to enhance junior secondary school students’ competence in writing procedural texts within the Indonesian context. A descriptive qualitative design was employed, involving a Bahasa Indonesia teacher and seventh grade students at MTs Jâ alHaq, Bengkulu. Data were collected through classroom observations, semi structured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings show that the Pair Check method was systematically embedded in lesson planning, instructional delivery, and assessment. During classroom practice, students alternated roles between problem solvers and checkers, supported by scaffolding and feedback from the teacher. Results further demonstrate that the method stimulated active participation, encouraged collaboration, and improved students’ ability to structure procedural texts, although challenges were noted in relation to time constraints and uneven student readiness. The study concludes that the Pair Check method offers an effective and contextually responsive pedagogical approach for teaching procedural writing in resource limited settings. Practical implications emphasize the need to design cooperative tasks aligned with genre structures, to explicitly train students in reciprocal roles, and to optimize class time to balance engagement with curriculum objectives.